Gender differences in risk preferences and stereotypes: Experimental evidence from a matrilineal and a patrilineal society - Andreas Pondorfer; Toman Omar Mahmoud; Katrin Rehdanz; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2014)
We use a controlled experiment to analyze gender differences in risk preferences and stereotypes about risk preferences of men and women across two distinct island societies in the Pacific: the patrilineal Palawan in the Philippines and the matrilineal Teop in Papua New Guinea. We find no gender differences in actual risk preferences, but evidence for culture-specific stereotypes. Like men in Western societies, Palawan men overestimate women's actual risk aversion. By contrast, Teop men underestimate women's actual risk aversion. We argue that observed differences in stereotypes between the two societies are determined by the different social status of women.
Keywords: C93; D81; J15; J16; 330; gender roles; culture; stereotype; experiment; risk aversion